A revision of mechanistic modeling of mild steel corrosion in H2S environments. (20th June 2021) - Abdar, Payman Sharifi; Hariri, Mohiedin Bagheri; Kahyarian, Aria; Nesic, Srdjan
Highlights: A revised mathematical model was developed to predict the corrosion rate of steel in H2 S environments. The buffering effect of H2 S was used in the model as governing cathodic mechanism. The effect of H2 S on the iron dissolution was introduced in the model. A good agreement between the experimental data and the present model was obtained. Abstract: In this study, a predictive model for the corrosion rate and the polarization response of bare steel in aqueous hydrogen sulfide (H2 S) environments based on H2 S dissociation and its buffering effect was developed. In this model, the hydrogen ion reduction is the only cathodic reaction. The results confirmed that the increased limiting cathodic current densities and the characteristic "double wave" behavior in the cathodic current of this system could be explained by hydrogen sulfide dissociation in the vicinity of the metal surface. The effect of hydrogen sulfide on the rate of iron dissolution reaction was also taken into account by introducing a reaction sequence involving sulfide intermediates into the calculations, parallel to the acidic iron dissolution reaction. The developed model was shown to be able to reasonably represent the characteristic electrochemical behavior of this system. Furthermore, the predicted corrosion rates are shown to be in good agreement with the available experimental data in the literature over a wide range of conditions.